Metal-insulator-metal plasmonic colour filters for CMOS image sensor applications - Pinton, N (2020)
Significant improvement in using plasmonic nanostructures for practical colour filtering and multispectral imaging applications is achieved by exploiting the coupling of surface plasmon polaritons with dielectric optical cavity resonances within a hexagonal array of subwavelength holes in a thin CMOS-compatible metal-insulator-metal (MIM) stack. This architecture overcomes the limitations of all previously reported plasmonic colour filters, namely poor transmission and broad band-pass characteristic, effectively providing a compact approach to selectively filter light. The physical insights established from the electromagnetic near-field patterns and parametric simulation studies are used to accurately tailor the optical properties of the filters.